Learning Plan Evaluation of Quality Assurance Biology Education - Anggis, Eka Vasia (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2023)
Higher education has regulations through standard set as quality assurance that must be fullfilled. This study aims to evaluate the learning planning of biology lecturers before carrying out lectures so that they can measure the achievement of the quality of biology learning planning. The research method is descriptive qualitative with QA evaluation technique. The results of the study showed that as a whole there was an increase in the percentage of fulfillment of the components of the lesson plan for a biology education course in 1 year, there were several components that had decreased so that control was needed in the form of solutions as the direction for further improvement programs. In conclusion, the results of the evaluation showed an increase in all components of the lesson plan compared to the following semester, but there were several components that needed improvement